Chemical and Morphological Characterization of the Pictorial Layer in 17th Century Portuguese Azulejos - Coentro, S. (2010)
Historic ceramic tiles (azulejos) are a valuable cultural asset in Portugal, being linked with its architecture for several centuries. In the 17th century, Portuguese azulejos were manufactured by the majolica process whereby an opaque white glaze was decorated with several pigments and then fired over a terracotta biscuit. Although most pictorial materials are inserted in the glaze, we often observe in the Portuguese azulejos a pictorial layer above the glaze. This is not because it was actually painted over it but simply because the paint never penetrated the glaze, not even upon firing. The morphology and chemical composition of such "unglazed" colours was investigated in a set of azulejos from the 17th century using Raman spectroscopy, micro energy-dispersive X-ray fluorescence (μ-EDXRF) and scanning electron microscopy with energy-dispersive X-ray fluorescence (SEM-EDXRF). The work focused mainly on the yellow, orange and quasi-black decorations whose exact chemical composition was doubtful.